2013
DOI: 10.1097/brs.0b013e31828864e6
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal Lumbar Interbody Fusion With rhBMP-2 in Spinal Deformity, Spondylolisthesis, and Degenerative Disease–Part 1

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Another study of 1,037 patients who underwent posterolateral fusion with rhBMP-2 noted few complications directly attributable to rhBMP-2 [24]. A recent study reported that the occurrence of BMP-related complications, such as seroma and ectopic bone, were rare [25]. The incidence of BMP-related complications in our study was low (4.8%) and all resolved with conservative treatment.…”
Section: Discussionmentioning
confidence: 41%
“…Another study of 1,037 patients who underwent posterolateral fusion with rhBMP-2 noted few complications directly attributable to rhBMP-2 [24]. A recent study reported that the occurrence of BMP-related complications, such as seroma and ectopic bone, were rare [25]. The incidence of BMP-related complications in our study was low (4.8%) and all resolved with conservative treatment.…”
Section: Discussionmentioning
confidence: 41%
“…The efficacy of TLIF with BMP is supported in the large series with long-term follow-up of Crandal et al 21 Reliable fusion and improved outcomes can be expected in adults undergoing TLIF for deformity, spondylolisthesis, and degenerative disease. Most complications occurred in patients with deformity.…”
Section: Discussionmentioning
confidence: 94%
“…At an average of 5 years of follow-up, fusion was achieved in 864 (99.1%) of 872 levels and seroma formation occurred in 0.4% of patients, ectopic bone growth in 0.6%, radiculitis in 1%, and symptomatic osteolysis or cage subsidence in none. 7,8 With such low rates, the study was inadequately powered to detect significant differences between dose groups. 5 Overall, although small risks exist, the current widespread use of BMP for TLIF procedures seems safe when appropriate surgical techniques are used.…”
Section: Discussionmentioning
confidence: 99%